On axiology of modern creative legislation in the sphere of criminal legal proceedings - Yuriy Vladimirovich Derishev (Сибирское юридическое обозрение, 2012)
The article is devoted to the analysis of a number of the bills offered by Inquiry committee of the Russian Federation, seriously correcting criminal procedure code of the Russian Federation concerning their value (utility) for modern domestic creative legislation and law enforcement.